Detecting the cold spot as a void with the non-diagonal two-point function - Masina, Isabella; Notari, Alessio (Journal of cosmology and astroparticle physics, 2010)
The anomaly in the Cosmic Microwave Background known as the “Cold Spot" could be due to the existence of an anomalously large spherical (few hundreds Mpc/h radius) underdense region, called a “Void” for short. Such a structure would have an impact on the CMB also at high multipoles ℓ through Lensing. This would then represent a unique signature of a Void. Modeling such an underdensity with an LTB metric, we show that the Lensing effect leads to a large signal in the non-diagonal two-point function, centered in the direction of the Cold Spot, such that the Planck satellite will be able to confirm or rule out the Void explanation for the Cold Spot, for any Void radius with a Signal-to-Noise ratio of at least 𝒪(10).
Gesehen am 23.05.2023